2021
DOI: 10.37190/ppmp/145420
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetic separation and reverse anionic flotation to concentrate fine particles of iron ore with high sulfur content

Abstract: The sulfur content in iron ore causes technical problems in the process of sintering iron ore in steel and alloys, and environmental problems in discharging the tailing. The major challenge in the iron ore processing plant is handling the finer particles. The key objectives of this research included the concentration of Band Narges Mine iron ore (< 150 µm) as well as the reduction of the sulfur content to achieve a marketable product. First, the mineralogical characterization of iron ore was established, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Hematite, ilmenite, and siderite are examples of weakly magnetic iron minerals that can be separated from less magnetic or non-magnetic gangue material using this technique. (11,19) high-intensity magnetic separation tests showed that ore contained mainly hematite as iron ore bearing mineral as only 30,36 % Fe corresponding to magnetite was recovered by high-intensity magnetic separation. The magnetic separation of the first group confirms it was more effective than the second group because the percentage of iron grade in the first group was increased.…”
Section: Effect Of Magnetic Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematite, ilmenite, and siderite are examples of weakly magnetic iron minerals that can be separated from less magnetic or non-magnetic gangue material using this technique. (11,19) high-intensity magnetic separation tests showed that ore contained mainly hematite as iron ore bearing mineral as only 30,36 % Fe corresponding to magnetite was recovered by high-intensity magnetic separation. The magnetic separation of the first group confirms it was more effective than the second group because the percentage of iron grade in the first group was increased.…”
Section: Effect Of Magnetic Separationmentioning
confidence: 99%
“…The production of fine particles from excessive grinding lowers product quality and recovery while also raising processing costs. (11,12,13) The most common application of magnetic separation is to separate magnetic iron ore such as magnetite and hematite from a variety of weaker or nonmagnetic materials. Since the magnetic separation process combines the benefits of high throughput and low operating cost with being ecologically friendly, it is crucial for upgrading such low-grade iron ores.…”
Section: Introductionmentioning
confidence: 99%
“…Hematite is the dominant mineral containing iron in Gol-e-Gohar. Sulfur impurities in the feed, which causes environmental problems in discharging the tailing [12], are due to iron-bearing minerals such as muscovite and biotite. Nearly 67 percent of the iron ore particles in the plant are smaller than 38 microns in diameter.…”
Section: Fobmentioning
confidence: 99%
“…in general, the gangue minerals in feldspar appear to have weak magnetic characteristics; just using a high-intensity magnetic separator can get a good result [23,26]. Most often, ferromagnetic materials such as magnetite are separated using dry or wet low-intensity magnetic separators, while paramagnetic minerals such as hematite are separated using high-intensity magnetic separators [27,28]. due to their low cost, high-intensity dry magnetic separators are becoming increasingly popular for the separation of paramagnetic materials [29].…”
Section: Introductionmentioning
confidence: 99%